Compressive Strength and Splitting Tensile Strength of Concrete Cube Using Magnetized Water - Adiama, M. M.; Yusuf, K. O.; Yusuf, A. K.; Moshood, M. A.; Sanusi, H. O. (ARID ZONE JOURNAL OF ENGINEERING, TECHNOLOGY AND ENVIRONMENT, 2024)
Report on cases of collapse of residential buildings and other structures are common in Nigeria which is normally due to structural failure, failure of the materials that were used for the construction and poor design. Buildings Collapse normally results to loss of lives and properties. The study was conducted to determine the effect of Magnetized Water (MW) on the Compressive Strength (CS) and Splitting Tensile Strength (STS) of Concrete Cubes (CC). MW is the water that has passed through magnetic field which could enhance proper hydration of concrete and improve the strength of CC. The CC was produced using sand (4.75 mm diameter), ordinary Portland cement, crushed granite (12 mm diameter) and MW. The mixing ratio of cement, sand and granite for the CC was 1:2:4 and water-cement ratio was 0.5. The treatments were T1 (concrete produced with Non-Magnetized Water -NMW and cured in MW treated for 1 minute), T2 (CC with MW treated for 1 minute and cured in NMW), T3 (CC with MW treated for 1 minute and cured in MW treated for 1 minute), T4 (CC with MW treated for 2 minutes and cured in NMW), T5 (CC with MW treated for 2 minutes and cured in MW treated for 2 minutes) and control T0 (CC produced with NMW and cured in NMW). CS and STS were determined after cured for 7, 14 and 28 days. The mean CSs after cured for 28 days T1, T2, T3, T4, T5 and T0 were 18.13, 22.00, 23.40, 19.07, 17.87 and 18.66 N/mm2, respectively. The mean STSs after cured for 28 days T1, T2, T3, T4, T5 and T0 were 1.33, 1.38, 1.59, 1.83, 1.21 and 1.32 N/mm2, respectively. MW increased the CS and STS by 25.40% and 37.57% of the concrete cubes, respectively. This shows that magnetized water is economical, simple and environmentally-friendly technology for the production of concrete cubes.